A cost-effectiveness analysis of denosumab for the prevention of skeletal-related events in patients with multiple myeloma in four European countries: Austria, Belgium, Greece, and Italy. (3rd August 2019) - Terpos, Evangelos; Jamotte, Aurelien; Christodoulopoulou, Alexandra; Campioni, Marco; Bhowmik, Debajyoti; Kennedy, Lisa; Willenbacher, Wolfgang
Abstract: Aim: The approved indication for denosumab (120 mg) was expanded in 2018 to include skeletal-related event (SRE) prevention in patients with multiple myeloma (MM). Therefore, a cost-effectiveness analysis was conducted comparing denosumab with zoledronic acid (ZA) for SRE prevention in patients with MM from the national healthcare system perspective in a representative sample of European countries: Austria, Belgium, Greece, and Italy. Methods: The XGEVA global economic model for patients with MM was used to calculate incremental cost-effectiveness ratios (ICERs) for denosumab vs ZA over a lifetime horizon. Clinical inputs were derived from the denosumab vs ZA randomized, phase 3 study ("20090482") in patients newly-diagnosed with MM, and comprised real-world adjusted SRE rates, serious adverse event (SAE) rates, treatment duration, dose intensity, progression-free survival (PFS), and overall survival (OS). Economic inputs comprised country-specific denosumab and ZA acquisition and administration costs, SRE and SAE management costs, and discount rates. Health utility decrements associated with MM disease progression, SRE and SAE occurrence, and route of administration were included. Results: Estimated ICERs (cost per quality-adjusted life-year [QALY] gained) for denosumab vs ZA in Austria, Belgium, Greece, and Italy were €26, 294, €17, 737, €6, 982, and €27, 228, respectively. Using 1–3 times gross domestic product (GDP) per capita per QALY as willingness to pay thresholds, denosumab was 69–94%, 84–96%, 79–96%, and 50–92% likely to be cost-effective vs ZA, respectively. Limitations: Economic inputs were derived from various sources, and time to event inputs were extrapolated from 20090482 study data. Conclusions: Denosumab is cost-effective vs ZA for SRE prevention in patients with MM in Austria, Belgium, Greece, and Italy, based on often-adopted World Health Organization thresholds. This conclusion is robust to changes in model parameters and assumptions. Cost-effectiveness estimates varied across the four countries, reflecting differences in healthcare costs and national economic evaluation guidelines.